Germany's Interest in Indonesia: Postcolonial Analysis of the Documentary Film Riders of Destiny - Hasta Aisyah Trida Pramita; Dwi Ardhanariswari Sundrijo (Soshum: Jurnal Sosial dan Humaniora, 2025)
This research critically examines Riders of Destiny (2019), a German documentary film about the pacoa jara, a horse racing tradition in Sumbawa, Indonesia, focusing on its portrayal of child exploitation. The film highlights the risks to child jockeys, such as injury and interrupted education, framing the practice as a violation of children’s rights. However, it oversimplifies the issue by neglecting the tradition’s historical, cultural, and economic context. Using postcolonial theory to analyse the film’s content, concept, and context, this research explores how the documentary reflects German interests in shaping global perceptions of non-Western cultures. The film’s content, shaped by selective interviews and imagery, emphasises the negative aspects of the practice, while its concept frames the tradition as a moral failure in need of reform. The context is largely ignored, with the film overlooking pacoa jara’s cultural significance within local communities and its role in family economics and social identity. This research concludes that Riders of Destiny serves as a tool for promoting Western child protection ideologies, positioning Germany as a moral authority while marginalising local cultural perspectives. This research does not intend to support child exploitation but rather seeks to explore how the practice of child jockeying is culturally perceived by the local community, which cannot be understood in a singular, Westernised way. Therefore, this study contributes to the existing literature on postcolonial theory by uncovering how media perpetuates modern forms of cultural influence that sustain postcolonialism.